Modeling extraction process using algebraic properties of differential spectra - Молодецька, Катерина Валеріївна (Technology audit and production reserves, 2013)
The following article is an example of modeling the one-dimensional diffusion process, which describes the extraction process, with the use of the method based on the algebraic properties of the differential spectra. The goal of the research was the modeling of an unsteady physical process to reduce the error from the modeling over a long period of time. Application of physical modeling of non-stationary processes in the area of differential images with the limited amount of discret in the differential spectrum, foresees imposition of the condition under which a modeling step is determined from the expression of estimation from above design errors according to Lagrange. We compared the results according to the known methods and found out that this process allowed the reduction of the calculable complication and the increase of the precision of the physical process design to the set level. The research results can be useful during the design stage of the extraction apparatuses for increasing the modeling process’s efficiency to optimize the extraction, formulation and solution of the production intensification problem. The usage of the method based on the algebraic properties of the differential spectra allows can more accurate reproduce the characteristics of the physical processes of extraction and the complexity of the relationship between their parameters.